2017
DOI: 10.1107/s2053230x1602063x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and X-ray analysis ofD-threonine aldolase fromChlamydomonas reinhardtii

Abstract: D-Threonine aldolase from the green alga Chlamydomonas reinhardtii (CrDTA) catalyzes the interconversion of several β-hydroxy-D-amino acids (e.g. D-threonine) and glycine plus the corresponding aldehydes. Recombinant CrDTA was overexpressed in Escherichia coli and purified to homogeneity; it was subsequently crystallized using the hanging-drop vapour-diffusion method at 295 K. Data were collected and processed at 1.85 Å resolution. Analysis of the diffraction pattern showed that the crystal belonged to space g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We have previously described the crystallization and preliminary X-ray analysis of CrDTA (Hirato, Goto et al, 2017). The crystal of CrDTA was obtained by the hanging-drop vapor-diffusion method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously described the crystallization and preliminary X-ray analysis of CrDTA (Hirato, Goto et al, 2017). The crystal of CrDTA was obtained by the hanging-drop vapor-diffusion method.…”
Section: Methodsmentioning
confidence: 99%
“…However, the highest resolution data could only be processed in the triclinic space group P1. The highest resolution diffraction data were processed with XDS (Kabsch, 2010), POINTLESS (Evans, 2011) and SCALA (Evans, 2006) within the CCP4 package (Winn et al, 2011) as described previously (Hirato, Goto et al, 2017).The analyzed diffraction pattern demonstrated that the crystal belonged to space group P1, with unit-cell parameters a = 64.79, b = 74.10, c = 89.94 A ˚, = 77.07, = 69.34, = 71.93 . The crystal contained four protein molecules in the asymmetric unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation